Metalloporphyrins in the management of neonatal hyperbilirubinemia - Stevenson, David K. (2009)
Neonatal jaundice in the first week of life is a common problem in newborns. It is due to an imbalance of bilirubin production and its elimination, which can lead to significantly elevated levels of circulating bilirubin or hyperbilirubinemia. Use of phototherapy and/or exchange transfusion are the current modes for treating neonatal hyperbilirubinemia and preventing any neurologic damage. These strategies, however, only remove bilirubin that has already been formed. Preventing the production of excess bilirubin may be a more logical approach. Synthetic heme analogs, metalloporphyrins, are competitive inhibitors of heme oxygenase (HO), the rate-limiting enzyme in bilirubin production, and their use has been proposed as an attractive alternative strategy for preventing or treating severe hyperbilirubinemia.